Focus on the Essential: Extracting the Decisive Energy Barrier of a Complex Process. Issue 20 (27th August 2019) - Aeschlimann, Simon; Neff, Julia; Bechstein, Ralf; Paris, Chiara; Floris, Andrea; Kantorovich, Lev; Kühnle, Angelika
Abstract: Molecular processes at surfaces can be composed of a rather complex sequence of steps. The kinetics of even seemingly simple steps are demonstrated to depend on a multitude of factors, which prohibits applying a simple Arrhenius law. This complexity can make it challenging to experimentally determine the kinetic parameters of a single step. However, a molecular‐level understanding of molecular processes such as structural transitions requires elucidating the atomistic details of the individual steps. Here, a strategy is presented to extract the energy barrier of a decisive step in a very complex structural transition by systematically addressing all factors that impact the transition kinetics. Only by eliminating these factors in the measurement the experimental data will follow an Arrhenius law and the barrier can be extracted for the single step. Using the system of 2, 5‐dihydroxybenzoic acid on calcite (10.4) as an example, the energy barrier is determined for the attachment‐assisted dissociation of molecular dimers in the structural transition from a striped to a dense molecular surface structure. This disentanglement approach is mandatory for a direct comparison with theoretical results and provides molecular‐level insights into the transition mechanism. Abstract : A strategy is presented to extract the energy barrier of an individual step in a very complex structural transition by systematically addressing all factors that impact the transition kinetics. Using the system of 2, 5‐dihydroxybenzoic acid on calcite (10.4) as an example, the energy barrier is determined for the attachment‐assisted dissociation of molecular dimers for a direct comparison with theoretical results.